Distinct consequences of amoxicillin and ertapenem exposure in the porcine gut microbiome. (October 2018) - Connelly, Sheila; Subramanian, Poorani; Hasan, Nur A.; Colwell, Rita R.; Kaleko, Michael
Abstract: The gut microbiome influences many, if not all, aspects of human health. Antibiotics, while lifesaving, have the unintended consequence of killing commensal microbiota inhabiting the gastrointestinal (GI) tract, which can lead to overgrowth of opportunistic pathogens such as Clostridium difficile and emergence of antibiotic-resistant organisms. Here, porcine models were developed to evaluate changes to the gut microbiome caused by two distinct types of beta-lactam antibiotics delivered via common administration routes, oral amoxicillin and intravenous ertapenem. Amoxicillin is one of the most often used broad-spectrum antibiotics, frequently prescribed to young children. Ertapenem, a carbapenem considered a last resort antibiotic, is used sparingly in humans and prohibited for use in animals. Cohorts of normal pigs (n = 5) were treated with amoxicillin (20 mg/kg, PO, BID) or ertapenem (30 mg/kg, IV, SID) for seven days. Microbiomes were evaluated using whole genome shotgun metagenomics analyses of fecal DNA collected prior to, during, and after antibiotic treatment. Each antibiotic resulted in significant and distinct changes in the microbiome, causing elimination of key commensal bacterial species and overgrowth of other, potentially pathogenic taxa. In addition, amoxicillin promoted propagation of a broad range of antibiotic resistance genes, many encoding efflux pump components and beta-lactamases, while ertapenem triggered emergence of genes encoding vancomycin resistance, and beta-lactamases, including the carbapenemase, IMP-27. Notably, microbiota alterations and antibiotic resistance gene propagation displayed unique patterns following exposure to amoxicillin or ertapenem. These data underscore the importance of understanding consequences of individual antibiotic use to predict and potentially mitigate adverse outcomes. The porcine models developed here can facilitate evaluation of therapeutic interventions to prevent antibiotic-mediated microbiome disruption. Highlights: Antibiotics cause collateral damage by killing commensal microbiota inhabiting the GI tract. Porcine models of antibiotic-mediated gut dysbiosis were established with oral amoxicillin and IV ertapenem. Each antibiotic resulted in distinct changes in the microbiome and emergence of different antibiotic resistance genes. Knowing consequences of individual antibiotics on the microbiome is key to predict and potentially mitigate adverse outcomes. The porcine models will facilitate evaluation of therapeutic interventions to prevent antibiotic-mediated microbiome disruption.